1991
DOI: 10.1098/rspb.1991.0089
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus borealis and Xenopus laevis 28 S ribosomal DNA and the complete 40 S ribosomal precursor RNA coding units of both species

Abstract: We have determined the nucleotide sequence of Xenopus borealis 28S ribosomal DNA (rDNA) and have revised the sequence of Xenopus laevis 28S rDNA (Ware et al., Nucl. Acids Res. 11, 7795-7817 (1983)). In the regions encoding the conserved structural core of 28S rRNA (2490 nucleotides) there are only four differences between the two species, each difference being a base substitution. In the variable regions, also called eukaryotic expansion segments (ca. 1630 nucleotides) there are some 61 differences, due to sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In this structure some of the proposed stems involve particularly well conserved sequences, others involve compensatory changes. As an example, the pairing of the first seven nucleotides at the very 5' end (nt 1-7) with nt 102-108 (nt numbering as in Figure 1) (24) has revealed that it contains a 12 nt sequence which can perfectly pair, allowing one G-U pairing, with Xenopus laevis 18S rRNA. This complementarity, shown in Figure 5, is highly significant in consideration of the small size of the RNA.…”
Section: Resultsmentioning
confidence: 99%
“…In this structure some of the proposed stems involve particularly well conserved sequences, others involve compensatory changes. As an example, the pairing of the first seven nucleotides at the very 5' end (nt 1-7) with nt 102-108 (nt numbering as in Figure 1) (24) has revealed that it contains a 12 nt sequence which can perfectly pair, allowing one G-U pairing, with Xenopus laevis 18S rRNA. This complementarity, shown in Figure 5, is highly significant in consideration of the small size of the RNA.…”
Section: Resultsmentioning
confidence: 99%
“…X79878 (Winnepenninckx et al 1995a); ecdysozoan (spider) Eurypelma (Aphonopelma) californica X13457 (Hendriks et al 1988); crinoids Endoxocrinus parrae, Z80951 (Littlewood et al 1997), and Metacrinus sp., AY275897 (Cohen et al 2004); chordate Xenopus laevis, X59734 (Ajuh et al 1991); sponge Soleniscus radovani, AF452017 (Manuel et al 2003 cf.…”
Section: Sequences Data-editing and Alignmentmentioning
confidence: 99%
“…These sites could have been caused by nucleotide insertion only in the Xenopus lineage. A previous investigation showed that the 28S rRNA gene of vertebrates had 11 " variable regions" with numerous polymorphic and gap sites between human and Xenopus (Ajuh et al, 1991). When examined under electron microscopic, these regions were thought to correspond to the loop regions in secondary structures of 28S rRNA (Ajuh et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…In amphibians, the nucleotide sequences of the rRNA precursor have been completely clarified in only the two tetraploid species of Xenopus (Ajuh et al, 1991). In the other amphibian species examined, only the short nucleotide sequences of some rDNA fragments have been Edited by Yoko Satta * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation